2004
DOI: 10.1016/j.femsle.2004.08.032
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of the dibenzofuran-degrading Actinobacteria carrying thedbfA1A2gene homologues isolated from activated sludge

Abstract: Thirteen dibenzofuran (DF)-utilizing bacteria carrying the DF terminal dioxygenase genes homologous to those of Terrabacter sp. strain DBF63 (dbfA1A2) were newly isolated from activated sludge samples. The amplified ribosomal DNA restriction analysis and the hybridization analyses showed that these strains were grouped into five genetically different types of bacteria. The sequence analyses of the 16S rRNA genes and the dbfA1A2 homologues from these five selected isolates revealed that the isolates belonged to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Other examples include Pseudomonas veronii PH-03 [Hong et al, 2004], Rhodococcus sp. strain DFA3 [Noumura et al, 2004], Janthinobacterium [Inoue et al, 2004], several strains of Janibacter sp. [Iwai et al, 2005;Jin et al, 2006;Yamozoe et al, 2004a, b], Nocardioides aromaticivorans IC177 [Inoue et al, 2005;, and Paenibacillus sp strain YK5 [Idia et al, 2006].…”
Section: Dioxin Degradation By Angular Dioxygenationmentioning
confidence: 99%
“…Other examples include Pseudomonas veronii PH-03 [Hong et al, 2004], Rhodococcus sp. strain DFA3 [Noumura et al, 2004], Janthinobacterium [Inoue et al, 2004], several strains of Janibacter sp. [Iwai et al, 2005;Jin et al, 2006;Yamozoe et al, 2004a, b], Nocardioides aromaticivorans IC177 [Inoue et al, 2005;, and Paenibacillus sp strain YK5 [Idia et al, 2006].…”
Section: Dioxin Degradation By Angular Dioxygenationmentioning
confidence: 99%
“…strain DFA10, both of which possess dbfA1A2 gene homologues, were isolated, and the gene organizations of the regions flanking the dbfA1A2 gene homologues were analysed. Sequence comparisons of these DNA regions among strains DBF63, DFA1 and DFA10 showed that the organizations of both pht and dbf-fln gene clusters were completely conserved (Noumura et al, 2004). These results strongly suggest that pDBF1 of strain DBF63 is a transmissible plasmid, and may play an important role in the distribution of FN-degradation genes.…”
Section: Discussionmentioning
confidence: 77%
“…It has been previously suggested that enzymes similar to DfdA YK3 are distributed among DBF-degrading actinobacteria (22), while enzymes similar to DbfA DBF63 have been recently reported in Rhodococcus strains, such as Rhodococcus sp. strain YK2 or DFA3 (44).…”
Section: Discussionmentioning
confidence: 99%